Risk and Return Analysis of Stocks Listed on the Kuala Lumpur Stock Exchange's (KLSE) Second Board - Ismail, Ahmad Zairin (1997)

(untitled)
Investors prefer to invest in securities or portfolios that can give them predictable expected return to their investment Other than the average return, the standard deviation and the coefficient of variation measures how the values are spread out This statistics indicate investment risk with respect to the portfolio foanation method. The findings are consistent to previous findings which suggest that securities with higher risk tead to have higher returns as compared to the lower risk securities. The findings show that risk diversification is achieved through portfolio formation. Portfolio beta, average return, standard deviation and coefficient of variation are relatively constant, irrespective of the method of portfolio formation.